Printing Devotion: Sufi Books and their Transregional Networks in an Age of Print - Elashmawy, Mariam (AUC Knowledge Fountain, 2022)
The production of printed books in the Muslim world is a story that encompasses an array of actors, spanning centuries, and taking place in remote, yet connected locales. This thesis provides an intellectual history of Ṣūfī print production of Islamicate mystical works in the nineteenth-twentieth centuries by examining three overlapping genres: poetry, Ṣūfī histories (hagiography), and litanies (aḥzāb). Texts such as the Dīwān of devotional poetry by Ibn al-Fāriḍ (d. 632/1234), the litany of Abū al-Ḥasan al-Shādhilī (d. 656/1258), Ḥizb al-baḥr, and Rashaḥāt ʿayn al-ḥayāt, a history of the Naqshbandiyya order by Fakhr al-Dīn ʿAlī (d. 940/1533), make up a mosaic of Ṣūfī texts that attracted the interests of printers, publishers, and the community of readers in Cairo, Istanbul, and Lucknow. By looking at the material and intellectual legacies of Ibn al-Fāriḍ, Abū al-Ḥasan al-Shādhilī and Fakhr al-Dīn ʿAlī, this thesis establishes the vibrant involvement of Ṣūfī groups in book culture from the medieval period to the age of print. Additionally, it investigates in what ways texts survive through the interest of Ṣūfī editors to print these particular texts; how they choose to present the material on the printed age; and how ideas move in society to the modern period. I attempt to piece together the story of the printed book and the interconnected afterlives of the author, editors, and publishers. This is done in order to understand how these various actors shaped and were, in turn, shaped by the production, distribution, reception, and survival of texts.